IMPLEMENTASI MODEL PEMURIDAN DAN MOBILITAS ANTAR GENERASI TERHADAP PERUBAHAN KARAKTER DAN INTERAKSI SOSIAL PADA ANAK-ANAK GENERASI Z - Lin, Steven; agus setiawan , Eko; Djaafar , Andre; Pasaribu, George Rudi Hartono (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The aim of this research is to determine the implementation of the discipleship model and intergenerational mobility on changes in character and social interactions among generation Z children at GBI Tabgha Batam. This research is research in the form of field research or field research is a type of research. This research is a qualitative descriptive research. The data in this research comes from primary and secondary data. Data collection methods use observation, interviews and documentation. Interviews were conducted with the community at the PkM location. The research results obtained in the implementation of discipleship and intergenerational mobility on changes in character and social interaction at GBI Tabgha Batam enable Gen Z children to have better character and also in their social interactions, building relationships through intergenerational discipleship is one of the models. ways that can be implemented so that relationships become more active and will influence character changes and better social interactions. This success is determined by other interesting activities that can support increased relations and mobility between generations. The inhibiting factor in efforts to maximize this is the previous generation's lack of understanding of this matter, the school environment and the home environment of generation Z